Adjusting the catalytic properties of cobalt ferrite nanoparticles by pulsed laser fragmentation in water with defined energy dose. Issue 1 (December 2017) - Waag, Friedrich; Gökce, Bilal; Kalapu, Chakrapani; Bendt, Georg; Salamon, Soma; Landers, Joachim; Hagemann, Ulrich; Heidelmann, Markus; Schulz, Stephan; Wende, Heiko; Hartmann, Nils; Behrens, Malte; et al.
Abstract Highly active, structurally disordered CoFe2 O4 /CoO electrocatalysts are synthesized by pulsed laser fragmentation in liquid (PLFL) of a commercial CoFe2 O4 powder dispersed in water. A partial transformation of the CoFe2 O4 educt to CoO is observed and proposed to be a thermal decomposition process induced by the picosecond pulsed laser irradiation. The overpotential in the OER in aqueous alkaline media at 10 mA cm−2 is reduced by 23% compared to the educt down to 0.32 V with a Tafel slope of 71 mV dec−1 . Importantly, the catalytic activity is systematically adjustable by the number of PLFL treatment cycles. The occurrence of thermal melting and decomposition during one PLFL cycle is verified by modelling the laser beam energy distribution within the irradiated colloid volume and comparing the by single particles absorbed part to threshold energies. Thermal decomposition leads to a massive reduction in particle size and crystal transformations towards crystalline CoO and amorphous CoFe2 O4 . Subsequently, thermal melting forms multi-phase spherical and network-like particles. Additionally, Fe-based layered double hydroxides at higher process cycle repetitions emerge as a byproduct. The results show that PLFL is a promising method that allows modification of the structural order in oxides and thus access to catalytically interesting materials.